Role of Mass Media in the Decision of the Consumer Desire to go for a Sustainable Fresh Water Alternative: A Case Study Conducted Within Jaffna Municipal Limit - Umashankar, K.; Latha, U. (Faculty of Agriculture University of Jaffna, Sri Lanka, 2015)
An urgency has developed over the last few decades in the safety and purity and the extent of freshness of ground water which apparently is the only source of drinking water in the peninsula. This ironically is due to the indifference, negligence and the carelessness of human activity. To check this state of affairs attempts are made to rein matters considered by many as too few too late. To clear the minds of the public of this trend of thought manipulation of the Mass media is essential. Rain water collection and preservation for protracted long term use is not new to the dry zone of Sri Lanka. Yet, of recent origin, water collected using traditional methods cannot be kept free of pollutants due to the water contact with the earth. Since the source of all pollutants is the earth as it is now, attempts are made to collect, protect and preserve rain water as best as possible. The answer is rain water harvesting systems. Viable and sustainable solution to insufficient supply of freshwater could be the rain water harvesting systems. The concepts though is lacking expression here in the peninsula is widely seen all over the world. However the hesitation, reluctance and the traditional suspicion of the body polity have to be engaged and addressed. For this purpose the Mass media could be harnessed. Mass media of all variety are likely to be important for informing better investment decisions on infrastructure. The question is how best these different sources could be employed to disseminate, technical installation and health information through the electronic and printed media and how and to what variant degree people are influenced through the media. This is the question which is addressed in the research conducted as to ascertain what socio economic factors influence the decision making trend of the people at large and how the media exposure of relevant factors affect the individual's decision. For this reason all available media material were compiled and a media exposure index was composed. The city of Jaffna was selected for this purpose and around 380 respondents were picked randomly but corresponding to the population of the relevant divisional secretarial division. A stratified purposive random sampling technique was used to pick the samples. To this end the data were collected on current water needs, health concern and household socio economic characteristics. The data were collected through three formats. They being open ended, open ended with prequalifying statements, and dichotomous choice. The collected data were analyzed within the frame work of Probit Regression model. The model was found to be significant at 1% a level. The results revealed that household desire to go for suitable fresh water alternative depends on media exposure index, household size, educational level of the household head, income of the household, and real estate extent. These factors again influenced positively and were statistically significant at 1%, 1%, 5%, 10% and 10% a level respectively. The mass media exposure index being the dependent variable in the model, it was found to be highly (1%) significant. Thus it is suggested that all up to date information on the relevant field be disseminated through the available media so that continuous and sustained information is made available to the community. This implies that the use of available media of all kind and types, to the maximum, to explain the level of effects of water pollution and the consequent health hazards generated in the peninsula, create awareness of the impending danger to residents clearly. This results in the decision of these people seeking a sustainable and durable solution to the emergency thus driving them towards an alternate solution like rain water harvesting systems. So that being informed, they become informative and in effect the civil society transforms slowly, steadily, gradually going through a paradigm shift into a more efficient and healthy one.
Keywords: Ground water pollution; Mass media exposure index; Probit regression model; Jaffna